KAJIAN PELAPUKAN GRANIT DAERAH LEATO BERDASARKAN ANALISIS XRD DAN SEM - Ronal Hutagalung; Aang Panji Permana; Dewi Rahmawaty Isa (EnviroScienteae, 2022)
Weathering is a natural process due to the work of exogenous forces both physically and chemically which results in the breakdown of rocks and constituent minerals into loose materials. Weathering can cause compact and resistant granite to move easily, causing rock fall in the Leato area, Gorontalo City. This study aims to assess the level of weathering of granite based on X-Ray Diffraction (XRD) and Scanning Electron Microscope Analysis (SEM) analysis. The research objectives will be achieved using two methods consisting of field surveys and laboratory analysis in the form of XRD and SEM analysis. Based on the results and discussion that granite rocks have undergone weathering. Evidence of weathering is clearly shown in SEM photos, namely weathering occurs at the edges of granite rocks.